Infusion of D1 Dopamine Receptor Agonist into Medial Frontal Cortex Disrupts Neural Correlates of Interval Timing - Parker, Krystal L.; Ruggiero, Rafael N.; Narayanan, Nandakumar S. (Frontiers in Behavioral Neuroscience, 2015)
Medial frontal cortical (MFC) dopamine is essential for the organization of behavior in time. Our prior work indicates that blocking D1 dopamine receptors (D1DR) attenuates temporal processing and low-frequency oscillations by MFC neuronal networks. Here we investigate the effects of focal infusion of the D1DR agonist SKF82958 into MFC during interval timing. MFC D1DR agonist infusion impaired interval timing performance without changing overall firing rates of MFC neurons. MFC ramping patterns of neuronal activity that refle¬ct temporal processing were attenuated following infusion of MFC D1DR agonist. MFC D1DR agonist infusion also altered MFC field potentials by enhancing delta activity between 1-4 Hz and attenuating alpha activity between 8-15 Hz. These data support the idea that the influence of D1-dopamine signals on frontal neuronal activity adheres to a U-shaped curve, and that cognition requires optimal levels of dopamine in frontal cortex.